Efeito da hidroxipropilmetilcelulose em argamassas leves térmicas à base de vermiculita expandida - Nascimento, Raquel Ferreira do (2021)
Insulating and low-density cementitious materials have been increasingly studied with the aim of improving thermal insulation conditions in buildings and the possibility of reducing the weight of buildings. One of the ways to develop this type of material is through the use of light aggregates or additives that allow, directly or indirectly, the incorporation of air. Thus, the present study aims to verify the influence of the use of hydroxypropylmethylcellulose (HMPC) on the thermal and mechanical properties of light mortars based on expanded vermiculite, with replacement of sand by light aggregate in the proportions of 0%, 20% , 40%, 60%, 80% and 100%, for sets of mortars with and without HPMC, the additive being used in the proportion of 0.2% in relation to the cement mass. To determine the properties of the fresh and hardened state of the mortars, the tests of compressive strength, bending tensile, adhesion tensile, water absorption by immersion, mass density, modulus of elasticity and water loss by evaporation. The thermal performance was obtained through the simplified method of NBR 15575-3 (ABNT, 2013) and through a simulator. The results indicate that the incorporation of HPMC causes an increase in the material's void index, promoting a reduction in mechanical strength and elastic modulus. This fact does not constitute an obstacle to its use, because, for a coating mortar, it is important to have flexibility in order to acquire a greater possibility of absorbing deformations. It is also noted that the incorporation of HPMC produces a mortar with lower mass density, reflecting in a lighter material with high thermal insulation capacity, in such a way that the 100% vermiculite composition can insulate approximately 20°C, while the complete system (mortar+brick+mortar) insulates approximately 43ºC, values that are higher when compared to the mortar without HPMC. Thus, it is concluded that the incorporation of HPMC allows an increase in thermal insulation in light mortars based on vermiculite, due to the increase in the void index provided by the use of the additive, directly influencing the mechanical properties of the material.